Treatment Efficacy of Various Maneuvers for Lateral Canal Benign Paroxysmal Positional Vertigo With Apogeotropic Nystagmus: A Randomized Controlled Trial - Lee, Hyun Jin; Jeon, Eun-Ju; Nam, Sungil; Mun, Seog-Kyun; Yoo, Shin-Young; Bu, Seong Hyun; Choi, Jin Woong; Chung, Jae Ho; Hong, Seok Min; Lee, Seung-Hwan; Kim, Min-Beom; Koo, Ja-Won; et al. (Clinical and experimental otorhinolaryngology, 2023)
Objectives The aim of this study was to determine the most effective treatment approach by comparing the impacts of various otolith reduction techniques in patients with apogeotropic lateral semicircular canal benign paroxysmal positional vertigo (LC-BPPV).Methods We performed a multicenter randomized prospective study from January to December 2015, involving 72 consecutive patients with apogeotropic LC-BPPV. The patients were divided into three treatment groups: therapeutic head-shaking (group A), the Gufoni-Appiani maneuver (group B), and the cupulolith repositioning maneuver (CuRM; group C). Each group underwent evaluation and treatment up to the fourth week. Treatment success was defined as the disappearance of positional vertigo and nystagmus.Results This study included 72 patients (49 male and 23 female), with a mean (±standard deviation) age of 55.4±13.5 years. The mean duration of vertigo experienced prior to treatment was 3.9±4.4 days. The mean latency and duration of nystagmus were 2.7±3.0 seconds and 47.9±15.8 seconds, respectively. The overall treatment frequency was 2.0±0.9. The number of treatments differed significantly among the three groups (P<0.05). After 4 weeks, the success rates for groups A, B, and C were 90.5%, 92.3%, and 100%, respectively. No significant difference was observed in the success rate across treatment methods and periods (P>0.05). However, CuRM was the only method with a 100% treatment success rate.Conclusion While no clear difference was observed among the three treatments for LC-BPPV, CuRM was found to be superior to the other approaches in the long term.